5 Thoracic aorta and pulmonary artery dimensions in patients undergoing ecg-gated computed tomography angiography. (15th May 2019) - Gentle, Andrew; Williams, Michelle C; Newby, David E; Roditi, Giles
Abstract : Introduction: Normal values for vascular dimensions are derived from echocardiography or magnetic resonance imaging (MRI), with limited data available on electrocardiogram (ECG)-gated computed tomography (CT) angiography. This abstract assesses aortic and pulmonary artery diameters and the factors affecting them, in patients undergoing CT as part of the SCOT-HEART (Scottish COmputed Tomography of the HEART) trial. Methods: Vessel diameters were measured on CT coronary angiography (CTCA) in six locations: annulus, sinus of Valsalva (SOV), sinotubular junction (STJ), ascending and descending aorta at right pulmonary artery level, and main pulmonary artery (MPA). The SCOT-HEART database provided demographics and cardiovascular risk factor information. Results: Images of 1000 patients (mean age 58±9, 58% male) were assessed. Amongst patients with normal coronary arteries and no history of hypertension, mean dimensions were: annulus short-axis 19±2mm, annulus long-axis 27±3 mm, SOV 31±4 mm, STJ 27±3 mm, ascending aorta 30±4 mm, descending aorta 22±2 mm, and MPA 23±3mm. Male sex, height, and body surface area (BSA) correlated with increases in all dimensions (p<0.001). Age correlated with aortic dimensions only (p<0.03). Patients with normal coronary arteries on CTCA had smaller aortic dimensions (p<0.001). Patients with hypertension had larger MPA and aortic dimensions (p<0.02), apart from at the annulus. Sex and BSA were independent predictors of all dimensions. Hypertension was an independent predictor of some aortic dimensions. Age was an independent predictor of all aortic dimensions, except the annulus. Conclusion: Aortic and pulmonary dimensions can be assessed on CTCA, with sex and BSA having an important impact on normal dimensions.